A Case of Haemorrhagic Herpes Zoster - P. Kuwar Chhetri; Ahmed Al Montasir; Renu Gupta; Shamsul Alam; Shafwanur Rahman; Fahim Rahman (University Library System, University of Pittsburgh, 2022)
Background: Varicella-zoster virus (HHV3) is one of the virus in herpes family. Herpes zoster results from the reactivation of varicella-zoster virus in the dorsal root ganglion. This reactivation occurs in immunocompromised conditions such as people with cancer, organ transplant recipients or those receiving chemotherapy, and people with HIV. Old age is also an important risk for the development of herpes zoster. Immunocompromised patients are at increased risk of VZV reactivation because of reduced T cell-mediated immunity. Emotional stress has also been mentioned as an associated factor in people with herpes zoster. The Classic clinical presentation consists of clear vesicular eruptions in dermatomal distribution which are painful. An immunocompromised individual may have frequent attacks of herpes zoster, cutaneous dissemination, organ involvement, and hemorrhagic herpes zoster. Haemorrhagic herpes zoster is an atypical form of herpes zoster develops in patients who are immunosuppressed and people of advanced age who are taking antiplatelets, and anticoagulants, and also in patients with thrombocytopenia due to any cause.  The most common Association of herpes zoster is observed with lymphocytic leukemia and less frequently with myeloid leukemia. Management icludes antiviral therapy along with management of haemorrhagic conditions. Case Report: A nondiabetic male of 60 years attended the medicine outpatients department with complaints of epistaxis for two days. No history of bleeding from other sites was evident. There was no history of trauma or taking of anticoagulants or antiplatelets. No history of fever. The patient was anaemic and an erythematous rash was evident along the right T6 dermatome. He was admitted to the general medicine ward. On the second day of his admission, our patient developed painful haemorrhagic bullous lesions over the right T6 dermatome resembling a bunch of grapes and erythematous popular lesions all over his body (Figure 1). The bullous lesions became larger in size in the subsequent two days of admission. On query, he mentioned that he had suffered from Varicella Zoster in his early childhood. Patients haemoglobin was 10.70 gm/dl, total count of white blood cell (WBC) was 13.20 K/ mm3 (normal value 4.00 - 11.00 K/ mm3), neutrophil and lymphocyte counts were 2.38 K/ mm3 (normal value 2.16 - 6.04 K/ mm3) and 10.38 K/ mm3 (normal value 0.6 - 3.06 K/ mm3) respectively. His platelet count was 5.00 K/ mm3 (normal value 150.00 - 400.00 K/ mm3). The patient denied skin biopsy. A diagnosis of haemorrhagic herpes zoster was made after a dermatology consultation and oral valacyclovir was started along with oral and topical antibiotics and regular dressings. After six units of platelet transfusion patients, the platelet count was raised to 30 K/ mm3. Peripheral blood film was suggestive of acute leukaemia. A bone marrow examination was suggestive of acute myeloid leukaemia. The patient was transferred to the haemato-oncology ward for further planning and management. Conclusion: Haemorrhagic herpes zoster may occur in different clinical conditions and one of them although rare, is acute myeloid leukaemia. Clinical scenario along with bone marrow and blood picture helps to reach a diagnosis in such cases.